Indonesia's Coffee Export Dynamics: Exploring the Impacts of Climate, Trade, and Productivity - Setiawan, Avi Budi; Yusuf, Mochammad (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2025)
As the fourth-largest coffee exporter worldwide, Indonesia contributes significantly to the global coffee trade while contending with challenges such as export volatility, trade barriers, and the impacts of climate change. This study aims to investigate the determinants of Indonesia’s coffee exports, focusing on productivity, trade barriers, and climate variability. This study employed the Error Correction Model (ECM) to analyze time-series data from 1989 to 2022, sourced from the FAO, WITS, and the World Bank. The findings indicate that, in the long run, coffee imports, trade openness, and the extent of harvested land area are positively correlated with export performance, while export taxes and increasing land temperatures exert negative effects. In the short run, productivity is associated with increased exports, whereas land area appears to have a negative relationship. These findings suggest that addressing trade barriers, improving land management, and enhancing trade openness are essential for strengthening export competitiveness.